Cellular retinol binding protein 1 could be a tumor suppressor gene in cervical cancer - Mendoza-Rodriguez, Mónica (e-Century Publishing Corporation, 2013)
Aims: Cervical Cancer (CC) is one of the most important health problems in women. It frequently presents genetic changes at chromosome region 3q21. This region contains the Cellular Retinol Binding Protein 1 gene (CRBP1) which has been implicated as an important element in the development of other types of cancer. The main goal of the present work was to determine the molecular alterations of CRBP1 and its relationship to CC. Methods: To determine the molecular alterations of CRBP1 gene in CC; twenty-six CC and twenty-six healthy cervix samples were evaluated for: 1) Copy number gain by real-time PCR analysis, 2) expression levels by an immunohistochemistry assay on tissue microarray, and 3) the methylation status of the CRBP1 promoter region. Results: The increase in CRBP1 copy number was observed in 10 out of the 26 CC samples analyzed, while healthy cervices samples showed no changes in the copy number. In addition, there was a lack of expression of the CRBP1 gene in an important number of the CC samples (17/26), and the CRBP1 gene promoter was methylated in 15/26 of the CC samples. Interestingly, there was a significant association between the lack of expression of the CRBP1 gene and its methylation status. Conclusions: The data indicates that, both activating and inactivating changes in the CRBP1 gene could be significant events in the development and progression of CC, and the lack of expression of the CRBP1 protein could be related with to the development of CC. We believe that there is enough evidence to consider to CRBP1 gene as a tumor suppressor gene for CC.